2014
DOI: 10.3329/bjvm.v12i2.21294
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Parameters of Native Sows in Selected Area of Bangladesh

Abstract: Reproductive performance is considered as one of the important factors affecting the productivity and economy of the pig farms. The objective of the study was to determine the reproductive parameters of gilts and sows by direct interview method using a pretested questionnaire in selected area of Bangladesh. A total of 20 pig farms having 60 gilts and 27 sows were included in this investigation. The present study revealed that, in native female pigs, the age at puberty was 229.0 ± 16.7 days, the oestrous cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
3
2
Order By: Relevance
“…The mean number of piglet's production in the present study was 6.1 ± 2.2. The mean number of piglet production of the present study is slightly lower than that of a previous study where the mean number of piglet production was 7.6 (Sinha, 2012), and higher than that of a previous study where the mean number of piglet production was 5.3 (Motaleb, 2013).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The mean number of piglet's production in the present study was 6.1 ± 2.2. The mean number of piglet production of the present study is slightly lower than that of a previous study where the mean number of piglet production was 7.6 (Sinha, 2012), and higher than that of a previous study where the mean number of piglet production was 5.3 (Motaleb, 2013).…”
Section: Discussioncontrasting
confidence: 86%
“…In the present study, the mean duration of oestrus in local and cross breed sows was 41.1 ± 3.1 and 36.8 ± 2.5 hours, respectively and it ranged from 15 to 72 hours. Similarly, Motaleb (2013) has reported that the duration of oestrus in native pigs was 37.9 hours. Duration of oestrus or heat is variable which may last only 12 hours in gilts or up to 60 hours or more in sows (Singleton and Diekman, 1990).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Newborn mortality generally occurred minor variations among different reproductive traits owing to difference in environment, feeding and management practices. Accordingly, FI (156 days) and WCI (38 days) in sows of Brazil (Mayor et al 2007), WEI (3-8 days) in Thailand (Tantasuparuk et al 2000), gestation length (114.5±1.0 days) in Bangladesh (Motaleb et al 2014), live litter size at birth (10.45) and weaning (9.44) in Czech Republic (Nevrkla et al 2016) and pre-wean mortality (18.2%) in North America (Holtkamp et al 2012) have been recorded previously. Nevertheless, most dependent variables in this study exhibited low values as compared to those revealed in an earlier report by Gourdine et al (2006) who maintained pigs in closed confinement under constant observation.…”
Section: Resultssupporting
confidence: 53%
“…The average litter sizes of 7.33±0.06 piglets (T1), 6.00±0.03 piglets (T2) and 6.33±0.08 piglets (T3) are more than 5.3 piglets reported by Motaleb et al (2014). The T1 result was similar to 7.33±3.4 piglets/litter for Sinha et al (2015).…”
Section: Litter Sizesmentioning
confidence: 73%